Evaluation of efficacy of septic screen in diagnosis of early onset sepsis - Kolhe, Shital; Mahajan, Puneet; Siddiqui, Sadaf; Sharma, Ashok; Rai, Rajesh (Indian Journal of Child Health, 2017)
Background: Clinical features of sepsis are non-specific in all neonates and a high index of suspicion is required for the timely diagnosis of sepsis. Although blood culture is the gold standard for the diagnosis of sepsis, reports are available after 48-72 h. Therefore, a practical septic screen for the diagnosis of sepsis is needed. Objectives: To study the maternal and neonatal risk factors for early onset neonatal sepsis and to evaluate the efficacy of septic screen in diagnosis of same. Methods: Total 51 inborn were selected on basis of presence of maternal and neonatal risk factors, clinical features consistent with infection. The following investigations were done: Total leukocyte count, absolute neutrophil count, immature/total Neutrophil (I/T) ratio, haematocrit, platelet count, C-reactive protein (CRP) (after 6 h), gastric lavage, Micro erythrocyte sedimentation rate (ESR), chest X-ray (after 6 h). Blood culture was sent for any neonate with septic screen positive or those developing clinical sepsis within 72 h of birth and were correlated with the gold standard test (BACTEC). Results: Our study consisted of 51 inborn babies with 61% males and 39% females, 41% preterm